Adenoviruses of subgenera B, C, D, and E modulate cell-surface expression of major histocompatibility complex class I antigens. - Pääbo, S (1986)
The immune defense against viral infections involves cytotoxic T lymphocytes that recognize viral products in the context of class I major histocompatibility complex (MHC) antigens. To evade such immune surveillance viruses may have evolved various strategies to manipulate the expression of class I antigens. Adenovirus 2 manufactures an early glycoprotein, E19, that binds to nascent class I antigens in the endoplasmic reticulum and impedes their transport to the cell surface. We now show that adenoviruses typical of all viral subgenera except the highly oncogenic subgenus A dramatically reduce the cell-surface expression of class I antigens. It has been shown that subgenus A viruses abolish class I antigen expression in transformed cells by reducing mRNA levels. Thus, all adenoviruses can modulate the cell-surface expression of class I antigens.